Intersections in the digital society: cancel culture, fake news, and contemporary public discourse - Picarella, Lucia (Frontiers in Sociology, 2024)
This article critically examines the intricate relationship between cancel culture and fake news, shedding light on their collective impact on current societies. The changing social landscape, marked by the transition from the ‘network society’ to the ‘platform society’, has given rise to unprecedented phenomena such as cancel culture. Rooted in social media complaints, cancel culture intersects with the dissemination of intentionally created false information, forming a complex web of dynamics. The study explores the multifaceted nature of cancel culture, its unintended consequences and the nuanced definitions surrounding it. The synthesis of erasure culture and fake news prompts critical reflections on the democratisation of information, the protection of fundamental rights and the potential risks to democracies of an unbridled online narrative. As digital networks continue to play a central role in everyday life, understanding and addressing these challenges is essential to maintaining a balanced discourse that upholds democratic values.